Ubiquitin–Proteasome System Is Required for Efficient Replication of Singapore Grouper Iridovirus - Huang, Xiaohong; Wei, Shina; Ni, Songwei; Huang, Youhua; Qin, Qiwei (Frontiers in Microbiology, 2018)
The ubiquitin–proteasome system (UPS) serves as the major intracellular pathway for protein degradation and plays crucial roles in several cellular processes. However, little is known about the potential actions of the UPS during fish virus infection. In this study, we elucidated the possible roles of UPS in the life cycle of Singapore grouper iridovirus (SGIV); a large DNA virus that usually causes serious systemic diseases with high mortality in groupers. Data from transcriptomic analysis of differentially expressed genes illustrated that expression of 65 genes within the UPS pathway, including ubiquitin encoding, ubiquitination, deubiquitination and proteasome, was up- or down-regulated during SGIV infection. Using different proteasome inhibitors, inhibition of the proteasome decreased SGIV replication in vitro, accompanied by inhibition of virus assembly site formation, and viral gene transcription and protein transportation. Over-expression of ubiquitin partly rescued the inhibitory effect of ubiquitin inhibitor on SGIV replication, suggesting that UPS was required for fish iridovirus infection in vitro. Viral or host proteins regulated by proteasome inhibition during SGIV infection were investigated with two-dimensional gel electrophoresis and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. Sixty-two differentially expressed proteins, including 15 viral and 47 host proteins, were identified after SGIV infection. The host proteins were involved in ubiquitin-mediated protein degradation, metabolism, cytoskeleton, macromolecular biosynthesis, and signal transduction. Among them, 11 proteins were negatively regulated upon MG132 treatment during SGIV infection. This is believed to be the first study to provide evidence that UPS was essential for fish virus infection and replication.